Entry deterrence, repeated auctions and divisibility of the object in sale - Peña Torres, Julio; Fernández Aguirre, Gabriel (Estudios de Economía, 2016)
This paper analyzes entry deterrence strategies at sequential multi-unit Englishtype repeated auctions, motivated by entry deterrence observed at a series of yearly auctions of fishing rights occurring since the early 1990s in the Chilean Sea Bass industrial fishery. It analyzes parametric configurations under which incumbent firms may have followed non-cooperative entry deterrence strategies or else may have colluded for that purpose. A two-stage competition model is developed. In the first stage there occurs sequential auctioning of multiple fishing rights; in the second stage, production rights are used to compete in a homogeneous-good Cournot market. The analysis focuses on the relationship between the number of incumbents, sources of competitive advantage for them (relative to potential entrants) and the number and productive size of the multiple production rights in sale. The core of the analysis lies in answering how does the divisibility of the object(s) in sale affect the possibilities of incumbent firms for deterring the entry of new rivals.